2016
DOI: 10.1097/opx.0000000000000995
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Non-Intrusive Assessment of Viewing Distance during Computer Use

Abstract: 27 28Purpose: to develop and test the sensitivity of an ultrasound-based sensor to assess the 29 viewing distance of visual display terminals operators in real time conditions. 30Methods: A modified ultrasound sensor was attached to a computer display to assess viewing 31 distance in real time. Sensor functionality was tested on a sample of 20 healthy participants 32 while they conducted four 10-minute randomly presented typical computer tasks (a match-33 three puzzle game, a video documentary, a task requirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Data were collected via MTurk and presented with Qualtrics [ 33 ] survey software. Assuming an average viewing distance of 55 cm [ 34 ], the 800 x 600 pixel stimulus images subtended 21.8 x 16.4 degrees on average for the MTurk participants. These dimensions held true for all the GW participants.…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected via MTurk and presented with Qualtrics [ 33 ] survey software. Assuming an average viewing distance of 55 cm [ 34 ], the 800 x 600 pixel stimulus images subtended 21.8 x 16.4 degrees on average for the MTurk participants. These dimensions held true for all the GW participants.…”
Section: Methodsmentioning
confidence: 99%
“…Many individuals experience visual fatigue due to prolonged use of digital devices, such as computers, for reading and writing purposes ( Carmichael, 1947 ; Argiles et al, 2016 ). Some studies have suggested that the viewing distance during near work may vary depending on the nature of different tasks ( Eastwood-Sutherland and Gale, 2011 ; Argiles et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many individuals experience visual fatigue due to prolonged use of digital devices, such as computers, for reading and writing purposes ( Carmichael, 1947 ; Argiles et al, 2016 ). Some studies have suggested that the viewing distance during near work may vary depending on the nature of different tasks ( Eastwood-Sutherland and Gale, 2011 ; Argiles et al, 2016 ). For example, a study that employed an ultrasound sensor device found that the viewing distances for game, text completion, and web search tasks were approximately 54.5 cm, which was shorter than that of a video task (62.3 cm) ( Argiles et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation